2014
DOI: 10.1002/hyp.10388
|View full text |Cite
|
Sign up to set email alerts
|

Relating nitrogen export patterns from a mixed land use catchment in NW Spain with rainfall and streamflow

Abstract: Abstract:The temporal variability in nitrogen (N) transport in the Corbeira agroforestry catchment (NW Spain) was analysed from October 2004 to September 2008. Nitrate (NO 3 -N) and total Kjeldahl nitrogen (TKN) loads and concentrations were determined at various timescales (annual, seasonal and event). The results revealed a strong intra-annual and inter-annual variability in N transport influenced by weather patterns and consequently by the hydrological regime. Mean annual export of total N in the catchment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…The evaluation of interventions showed that policy-makers still struggle to set appropriate goals for water quality improvement, particularly in heavily human-impacted watersheds. Studies in Europe and the United States showed that interventions like reduced N inputs mainly in agricultural land use do not immediately result in declining riverine NO 3 -N concentrations (Bouraoui and Grizzetti, 2011;Sprague et al, 2011;Howden et al, 2011) and fluxes (Worrall et al, 2009), although fast responding headwaters have been reported as well (Rozemeijer et al, 2014).…”
mentioning
confidence: 99%
“…The evaluation of interventions showed that policy-makers still struggle to set appropriate goals for water quality improvement, particularly in heavily human-impacted watersheds. Studies in Europe and the United States showed that interventions like reduced N inputs mainly in agricultural land use do not immediately result in declining riverine NO 3 -N concentrations (Bouraoui and Grizzetti, 2011;Sprague et al, 2011;Howden et al, 2011) and fluxes (Worrall et al, 2009), although fast responding headwaters have been reported as well (Rozemeijer et al, 2014).…”
mentioning
confidence: 99%
“…In general, model simulations can be considered satisfactory (R 2 > 0.5; NSE > 0.5) according to the criteria given by Moriasi et al [20], indicating that it is a valid tool to identify crucial pollution areas within the catchment. Although simulated NO 3 -N yield replicated the measured data trend quite well (Figure 2), the model underestimated the measured values during the autumn-winter 2005/2006 when high nitrate levels in stream were observed [16]. This fact may be due to underestimation of some discharge peaks in this period [21], which led to underestimating corresponding NO 3 -N yield because NO 3 -N, like other water quality parameters, depends on hydrological processes, and therefore errors in discharge simulations are magnified in their simulation.…”
Section: Swat Model Performance For Nitrate Yield Estimation At Catchmentioning
confidence: 63%
“…However, forest areas are not fertilized. The annual N input to the catchment is approximately 37.8 kg N ha −1 , 49% comes from organic fertilizers, 16% from inorganic fertilizers, 2% from population centres and the remaining 33% of atmospheric deposition [15,16].…”
Section: Study Area and Datamentioning
confidence: 99%
“…For examples, in the 2008/2009 hydrological year, TN, N-NO 3 and TKN concentrations were significantly lower in spring than summer, when it reached the highest daily flow-weighted mean TKN concentration, which was notably influenced by two large rainfall-runoff events in July of 2009. The summer of the 2008/2009 water year was characterized by elevated rainfall in July (170% higher than mean rainfall for July in the period 1983-2009) concentrated in two intense rainfall events, which caused high surface runoff and particulate material delivery to the stream [11] and consequently high TKN concentrations were observed. However, the very dry autumn 2007/2008 led to very low TKN concentrations, very similar to those observed in summer.…”
Section: Intra-annual Variation Of N Concentrationsmentioning
confidence: 99%
“…In addition, the N concentrations display wide variability within the same catchment. For example, for a given rainfall event, the N concentrations may differ greatly at different times of the year [11,12]. Climate and land use change is expected to alter the transfer of nutrients from land to water, although the results are controversial [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%